Pengaruh Citra Merek, Suasana Toko, dan Kualitas Produk terhadap Keputusan Pembelian Produk Eiger di Eiger Adventure Store Damar Padang - Indra Guspi Saputra; Maizul Rahmizal (JURNAL RISET MANAJEMEN (JURMA), 2025)
This research aims to examine the influence of brand image, character atmosphere and product quality on purchasing decisions for Eiger products at the Eiger Adventure Store Damar Padang. This type of research is quantitative, where this research uses numerical data and the research process emphasizes objective measurement of results using analysis. statistics. The population in this research is consumers shopping at the Eiger Adventure Store Damar Padang. The sampling technique used was simple random sampling. The number of samples was 100 people obtained using the Slovin formula. The type of data used in this research is quantitative and qualitative data. Meanwhile, the data sources are primary and secondary data sources. The data analysis technique uses multiple linear regression using the SPSS version 21.00 program. The hypothesis was tested using the t test at α = 0.05. The results of this research show that Brand Image has a positive and significant influence on the Eiger Purchase Decision at the Eiger Adventure Store Damar Padang, the Store Atmosphere has a positive and significant influence on the Eiger Purchase Decision at the Eiger Adventure Store Damar Padang, and Product Quality has a positive and significant influence on the Eiger Purchase Decision at Eiger Adventure Store Damar Padang.